2010
DOI: 10.1017/s0007114510000243
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of xylo-oligosaccharides and fructo-oligosaccharides in streptozotocin-induced diabetic rats

Abstract: The beneficial influences of xylo-oligosaccharides (XOS) obtained from alkali-pretreated corncob and fructo-oligosaccharides (FOS) obtained from cane sugar were evaluated in experimental diabetes. These oligosaccharides were supplemented at 10 % (w/w) in the basal diet of streptozotocin-induced diabetic Wistar rats, while the control rats were fed with a basal diet for a period of 6 weeks. Both the oligosaccharides exerted favourable influences in diabetic rats by significantly improving body weight and reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 38 publications
5
87
0
Order By: Relevance
“…Table 3 Whole-body (wet weight basis, %), liver composition (g 100 g -1 liver), hepatosomatic and visceral somatic indices of gilthead sea bream fed the experimental diets at two In streptozotocin-induced diabetic rats, FOS were able to improve glucose tolerance by reducing hyperglycaemia (Gobinath et al 2010). Such an effect was not observed in the present study, whereas plasma glucose levels in prebiotic-fed fish were similar to the control group or even higher.…”
Section: Discussionmentioning
confidence: 45%
“…Table 3 Whole-body (wet weight basis, %), liver composition (g 100 g -1 liver), hepatosomatic and visceral somatic indices of gilthead sea bream fed the experimental diets at two In streptozotocin-induced diabetic rats, FOS were able to improve glucose tolerance by reducing hyperglycaemia (Gobinath et al 2010). Such an effect was not observed in the present study, whereas plasma glucose levels in prebiotic-fed fish were similar to the control group or even higher.…”
Section: Discussionmentioning
confidence: 45%
“…In a randomized double-blind clinical trial with type 2 diabetic patients in Taiwan, XOS supplementation was administered for eight weeks, and this treatment was effective in reducing the blood lipid profile and blood glucose levels [42]. XOS also exhibits hypoglycemic and hypocholesterolemic properties, and complications in kidney tissues improve by regulation of antioxidant enzymes in streptozotocin (STZ)-induced diabetic rats [43]. …”
Section: Discussionmentioning
confidence: 99%
“…In these studies, XOS was shown to significantly increase the population of bifidobacteria and lactobacilli in the cecum (10,11). An in vitro study using swine fecal microbiota showed the highest SCFA production during fermentation of XOS (12).…”
mentioning
confidence: 98%